Seberapa Membantu Laporan Keuangan Dalam Penilaian Untuk Merger Dan Akuisisi - Danish Bahir; Fadi Rajendra (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2023)
Performance according to Mulyadi (2001: 416) is: a description of the level of achievement of the implementation of an activity / program / policy in realizing the goals, objectives, vision and mission of the organization contained in the formulation of strategic planning (strategic planning) of an organization. According to Sony Yuwono (2003:23) performance appraisal is an act of evaluating various activities in the value chain in the company. Most company performance appraisals use financial information as a single indicator in measuring company performance and have been widely used. Dwiyanto (2007: 36), the definition of financial performance appraisal is the determination of certain measures that can measure the success of a company in generating profits.